2020
DOI: 10.1088/1361-6595/abc6f6
|View full text |Cite
|
Sign up to set email alerts
|

Pulse length selection for optimizing the accelerated ion flux fraction of a bipolar HiPIMS discharge

Abstract: The effect on the energy distributions of metal and gas ions in a bipolar high-power impulse magnetron sputtering (HiPIMS) discharge as the negative and positive pulse lengths are altered are reported. The results presented demonstrate that the selection of the pulse lengths in a HiPIMS discharge is important in optimizing the amount of accelerated ions. A short enough negative pulse is needed so that ions do not escape to the substrate before being accelerated by the positive pulse that follows the main negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 33 publications
2
32
1
Order By: Relevance
“…The apparently contradictory results, in terms of the effect of positive target voltage on the film's properties, reported in the literature, could be due to some different deposition conditions and/or deposition systems used (e.g., different pulsing and/or magnetic field configurations). The influence of pulsing configuration on the fraction of accelerated ions towards a grounded mass spectrometer was recently reported by Viloan et al [22]. According to their work, the fraction of ions, accelerated to energies corresponding to the full positive target potential, is close to 100% when the duration of the negative and positive pulses is properly selected.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The apparently contradictory results, in terms of the effect of positive target voltage on the film's properties, reported in the literature, could be due to some different deposition conditions and/or deposition systems used (e.g., different pulsing and/or magnetic field configurations). The influence of pulsing configuration on the fraction of accelerated ions towards a grounded mass spectrometer was recently reported by Viloan et al [22]. According to their work, the fraction of ions, accelerated to energies corresponding to the full positive target potential, is close to 100% when the duration of the negative and positive pulses is properly selected.…”
Section: Introductionmentioning
confidence: 90%
“…In order to minimize the substrate's influence on the indentation data, the indentation depth was kept below 40 nm (10% of the films' thickness). Previous studies have shown that the fraction of accelerated ions during bipolar-HiPIMS strongly depends on the pulsing configuration [22]. During bipolar-HiPIMS, the fraction of accelerated ions can be accurately controlled by keeping constant the duration of negative pulse and by varying the duration of the positive pulse.…”
Section: Films Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of pulsing parameters (in both the positive and negative phases) was based on the experiments published in [11], where it is demonstrated that the application of a short negative pulse followed by a larger positive pulse maximizes the fraction of positive ions accelerated during the positive phase. As the negative pulse time is longer than the time-of-flight of the metal ions, these ions reach the substrate without being accelerated.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of changing the length of the negative pulse, , and the positive pulse, , is investigated in Paper III. It was observed that the accelerated ion flux fraction due to the application of Urev increases with a decrease in and a sufficient increase in [121]. A long allows more ions generated during the HiPIMS pulse to arrive at the substrate without being affected by Urev.…”
Section: Bipolar Hipimsmentioning
confidence: 99%